Qualitative Evaluation of Scaffolded Teaching Materials in Business Analysis Classes: How to Support the Learning Process of Young Entrepreneurs - Hiroko Oe; Chizuru Tanaka (MDPI AG, 2023)
The purpose of this study is to test the usefulness of the scaffolding materials and to provide practical recommendations for entrepreneurship education. Following the framework of social learning theory and a semi-structured questionnaire that was developed based on the results of a literature review concerning entrepreneurial creativity and competency issues, a thematic analysis was conducted to analyse how the template materials developed alongside the affected motivation and learning outcomes of the author's learners. The results highlighted the following. The participants recognised that the established model of business analysis taught in lectures is a generic model that discards non-economic factors and real business situations, and that potential entrepreneurs in developing countries should pay more attention to the sociocultural context of which they are potentially or explicitly aware. The participants also appreciated that the scaffolding materials helped them understand the general conceptual model in a familiar and practical context, and that the process and output of filling out the template stimulated class discussion, deepened their understanding, and influenced their own awareness. Furthermore, they greatly appreciated that the process of discussing the template allowed them to share and reflect on their own entrepreneurial activities through storytelling, which enhanced their learning through the propagation of their own awareness. Thus, the development of scaffolding materials that focus on reflection could play an important role in reinforcing the learning outcomes of business analysis and imprinting them in students' minds by encouraging them to think critically about prominent models in textbooks. The results of this study suggest that social learning theory can serve as an effective guide for the design, review, and improvement of learning support measures.